1998
DOI: 10.1172/jci1830
|View full text |Cite
|
Sign up to set email alerts
|

Protection from reoxygenation injury by inhibition of rac1.

Abstract: We demonstrate that adenoviral-mediated gene transfer of a dominant negative rac1 gene product (N17rac1) inhibits the intracellular burst of reactive oxygen species (ROS) that occurs after reoxygenation of vascular smooth muscle cells. In contrast, expression of a dominant negative ras gene (N17ras) had no effect. Challenge of control cells and cells expressing N17rac1 with a direct oxidant stress produced an equivalent increase in intracellular ROS levels and subsequent cell death. This suggests that N17rac1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 40 publications
3
104
0
1
Order By: Relevance
“…These kinases may be regulated further by ROS from NAD(P)H oxidase, which requires Rac1 for activity (46). Inhibition of Rac1 lessens both ROS production and reoxygenation injury (58).…”
Section: Reactive Species In Intracellular Signalingmentioning
confidence: 99%
“…These kinases may be regulated further by ROS from NAD(P)H oxidase, which requires Rac1 for activity (46). Inhibition of Rac1 lessens both ROS production and reoxygenation injury (58).…”
Section: Reactive Species In Intracellular Signalingmentioning
confidence: 99%
“…Although low level production of ROS in non-phagocytic cells seems to be beneficial and is involved in several regulatory cellular processes including gene expression, higher quantities of ROS are implicated in the pathogenesis of atherosclerosis through activating VSMC proliferation and migration [1,13,14]. It is welldocumented that endothelial ROS production increases by several stimuli including pulsatile stretch, hypoxia-reoxygenation and phorbol esters [15][16][17]. However, the precise role of NAD(P)H oxidase in endothelial cell growth remains to be determined.…”
Section: Nad(p)h Oxidase Is Predominantly Expressed In Phagocytic Celmentioning
confidence: 99%
“…The full-length rat endothelial cell p22-phox cDNA was generated using the primers and experimental conditions as previously described [15]. The PCR product was sequenced and cloned in sense and antisense orientations into the expression vector pcDNA 3.1 (Invitrogen).…”
Section: Cmec Transfectionmentioning
confidence: 99%
“…6 Ischemia/reperfusion (I/R) and hypoxia/reoxygenation (H/ R) result in the production of ROS within tissue or cells. 2,7,8 The rac1 small GTPase is an important regulator of ROS production within cells under these circumstances. 7 Rac1 belongs to the rho family of small GTP binding proteins and its role in the production of ROS in phagocytic cells such as neutrophils is well established.…”
Section: Introductionmentioning
confidence: 99%
“…Rac proteins, in particular rac1, function similarly in nonphagocytic cells, 1,12 and such rac1-regulated ROS have been implicated in a variety of cellular processes including growth, migration, and transformation. 2,8,[12][13][14][15][16][17] We have recently shown that rac1-regulated ROS production also mediates apoptosis in response to I/R. 7 Hepatocyte growth factor (HGF), which was initially isolated as a potent mitogen for hepatocytes, is now known to be a broad-spectrum mitogen for a variety of cell types.…”
Section: Introductionmentioning
confidence: 99%